Imaging of intracranial atherosclerotic plaques using 3.0 T and 7.0 T magnetic resonance imaging—current trends and future perspectives - Wu, Fang (Cardiovasc Diagn Ther, 2020)
Intracranial atherosclerotic disease (ICAD) is one of the most common causes of ischemic stroke and carries a relatively high risk of stroke recurrence. Advances in high-resolution magnetic resonance imaging (HRMRI) techniques of intracranial arteries now have made it possible to directly visualize atherosclerotic plaque itself, allowing detailed assessments of plaque morphology and components. Currently available intracranial HRMRI could be performed with 2-dimensional (2D) and 3D acquisitions, and multicontrast weightings in clinically reasonable scan times. Until now, HRMRI research of ICAD has focused on the identification of plaque vulnerability, and the relationship between plaque characteristics and ischemic stroke. HRMRI at ultra-high-ﬁeld strength (7.0 T) holds promise in better visualizing intracranial vessel walls, as well as identifying early lesions and total burden of ICAD. As a result, intracranial HRMRI provides great insights into pathology of intracranial atherosclerotic plaques, stroke mechanisms, and future stroke risk. In this article, we will review the technical implementation, preclinical research, clinical applications, and future directions of HRMRI for the evaluation of ICAD at 3.0 T and 7.0 T.